Can We Accurately Time the Administration of Antenatal Corticosteroids for Preterm Labor?. (7th November 2016) - Aghajanian, Paola; Nguyen, Quy T.; Greene, Naomi H.; Gregory, Kimberly D.
Abstract : Background . Accurate timing of antenatal corticosteroids (ACS) has resulted in improved neonatal outcomes. Objectives . Our primary objective was to determine predictors for optimal timing of ACS in women presenting with spontaneous preterm labor. Study Design . A retrospective cohort study of women receiving ACS for spontaneous preterm birth was conducted. Women were included if they presented with preterm labor or preterm premature rupture of membranes. Accurate timing of ACS was defined as administration within 7 days of delivery. Maternal demographic and obstetrics characteristics were compared between the groups receiving ACS ≤7 days and >7 days from delivery. Statistical analyses were performed using parametric and nonparametric tests. P < 0.05 was considered significant. Results . The study included 215 subjects. Median latency from ACS administration to delivery was 6 days (IQR 32). Accurate timing of ACS occurred in 113 (53%) women and was associated with rupture of membranes (OR 13.8, 95% CI 5.9–32.6), cervical change (OR 7.1, 95% CI 3.0–17.1), and cervical dilation ≥ 2 cm (OR 3.9, 95% CI 1.5–10.3). Conclusions . Rupture of membranes, cervical change, and cervical dilation ≥ 2 cm were strong predictors of optimal timing. 53% of women with preterm labor received ACS optimally.